2015
DOI: 10.1142/s1088424615500418
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carboxylated chlorophylls and their application as functional materials

Abstract: A series of chlorophyll derivatives possessing a carboxy group were synthesized aiming at their application as sensing materials and to dye-sensitized solar cells (DSSCs). Their absorption and fluorescence responses to amine concentrations in THF and photovoltaic performance of DSSCs on TiO 2 films were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…As one of the most abundant natural photosynthetic pigmentsonearth, chlorophylls (Chls) were selected to convert solar energy into chemical energy based on absorbing sunlight and transferring absorbed energy,d ue to the delocalization of their excited electrons around the p-conjugated tetrapyrrole ring. [8][9][10] The remarkable properties of the charge-transfer ability of Chls have been reported previously.I tw as shown that they could form aggregates to efficiently captures unlight and transport chargec ompared with their monomers. Such properties of Chl derivatives have been applied in solar cells, [11][12][13] energys torage, [14] and photocatalytic hydrogen evolution.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…As one of the most abundant natural photosynthetic pigmentsonearth, chlorophylls (Chls) were selected to convert solar energy into chemical energy based on absorbing sunlight and transferring absorbed energy,d ue to the delocalization of their excited electrons around the p-conjugated tetrapyrrole ring. [8][9][10] The remarkable properties of the charge-transfer ability of Chls have been reported previously.I tw as shown that they could form aggregates to efficiently captures unlight and transport chargec ompared with their monomers. Such properties of Chl derivatives have been applied in solar cells, [11][12][13] energys torage, [14] and photocatalytic hydrogen evolution.…”
Section: Introductionmentioning
confidence: 63%
“…This potential Z‐scheme of particular concern in photoinduced electron‐transport chain processes led us to design dual photoexcitation‐based photocatalysts. As one of the most abundant natural photosynthetic pigments on earth, chlorophylls (Chls) were selected to convert solar energy into chemical energy based on absorbing sunlight and transferring absorbed energy, due to the delocalization of their excited electrons around the π‐conjugated tetrapyrrole ring [8–10] . The remarkable properties of the charge‐transfer ability of Chls have been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Direct introduction of a carboxy group on the Chl macrocycle as in Chl‐15, 16, and 17 showed improved efficiency compared with the reported Chl‐2 but later Chl derivatives with C3‐acrylic acid was found to show better performance . The effects of tetrapyrrole skeleton (BChl‐2 and 3), steric and electronic substituent at the C20‐ (Chl‐18, 19, 20, and 21) and C13‐position (Chl‐18, 22, and 23), central metal ((Zn)Chl‐18, 24, and 25), C17‐ (Chl‐26, 27, 28, and 29) or C13/15/17‐alkyl chain (Chl‐30, 31, 32, and 33) were investigated in detail, and PCE of 8% was achieved after optimization. Because a carboxy group at the C3‐position of Chl‐15 caused PCE of 3.8% and increased to 6.5% upon insertion of an ethenylene group between the carboxy group and the C3‐position of the Chl π‐skeleton as in Chl‐18, the effect of spacer length and π‐conjugation was further investigated.…”
Section: Application Of Carboxylated Chlorophyll Derivatives To Dsscsmentioning
confidence: 93%
“…For introducing the C3 2 -carboxylic acid moiety as a binding and electron-injecting site to TiO 2 , Wittig reaction of the C3-formyl group with (tertbutoxycarbonylmethylene)triphenylphosphoran, and the following cleavage of the tert-butyl ester in TFA were applied. [51] To obtain tert-butyl ester 7 from 8, initial Wittig reaction (8→9: 86%) followed by ester formation (9+Car-COOH: 69%) showed a slightly better yield compared to 8→6→7 (60% × 90% = 54%). The subsequent cleavage of tert-butyl ester in 7 gave Dyad-COOH in 80% yield, which was better than the direct conversion of C3-formyl to C3-acrylic acid group by excess maleic acid [52] resulting in 41% yield in the case of carotenoid-chlorin 6 to Dyad-COOH.…”
Section: Design and Synthesis Of Dyad Sensitizersmentioning
confidence: 98%